2022
DOI: 10.30827/digibug.72270
|View full text |Cite
|
Sign up to set email alerts
|

Las Redes Sociales y su Influencia en la Salud Mental de los Estudiantes Universitarios: Una Revisión Sistemática

Abstract: Área o categoría del conocimiento: Educación SuperiorResumen: Los problemas de salud mental y su relación con las redes sociales son fenómenos relevantes de estudiar dada su alta incidencia y utilización entre los estudiantes universitarios. El objetivo de esta revisión sistemática fue determinar la influencia de las redes sociales en la salud mental de los estudiantes universitarios y establecer factores de riesgos y posibles impactos. La búsqueda se realizó siguiendo la metodología PRISMA en los buscadores W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
(83 reference statements)
0
0
0
2
Order By: Relevance
“…It generates high EE, which can cause serious long-term consequences for mental health [47]. The results presented are consistent with a recent systematic review which found that high levels of internet and social network use in university students were correlated with the presence of the fear of missing out (FOMO), anxiety, depression, stress, internet addiction, learning disabilities, and sleep disorders [48].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It generates high EE, which can cause serious long-term consequences for mental health [47]. The results presented are consistent with a recent systematic review which found that high levels of internet and social network use in university students were correlated with the presence of the fear of missing out (FOMO), anxiety, depression, stress, internet addiction, learning disabilities, and sleep disorders [48].…”
Section: Discussionsupporting
confidence: 88%
“…The Exhaustion Interpretation Table (EES-Int) [43] includes a scale that was created in 2021 to interpret the results of the ECE. The score of the ECE is interpreted through the EES-Int Scale in four levels: low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), medium (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), high (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and very high (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). It describes the indicators of emotional exhaustion under each score level's cognitive, affective, and social-interactional processes.…”
Section: Instrumentsmentioning
confidence: 99%
“…La calidad de los estudios (tabla 2), estuvo determinada mediante la escala Newcastle-Otawa (NOS) adaptada para estudios transversales, la NOS se encarga de evaluar la calidad considerando el contenido, diseño e interpretación con confiabilidad y validez. Esta escala valora tres dimensiones: selección, comparabilidad y resultado, distribuidas en siete categorías a las cuales se les puede asignar un total de nueve estrellas si el estudio cumple con los criterios establecidos, una asignación máxima de cuatro, dos y tres estrellas para las dimensiones selección, comparabilidad y resultados respectivamente (Martínez et al, 2022).…”
Section: Pág 1839unclassified
“…La tarea psicosocial de la etapa de la adolescencia supone el desarrollo de una identidad socialmente validada (Davis, 2013;. Los adolescentes contemporáneos, utilizan de manera intensiva (Martinez-Libano et al, 2022). las redes sociales como espacio de socialización (Arab y Díaz, 2015;Oliva Marañon, 2012;Quirós-Ramírez, 2018).…”
Section: Conclusión Y Discusiónunclassified